ISLAM AS A POLITICAL FORCE READING THE DIRECTION OF ISLAMIC POLITICAL MOVEMENT IN INDONESIA TOWARDS DEMOCRACY - Prayitno, Adi (STAI Asy-Syukriyyah, 2025)
This study explores the role of Islam in Indonesia's politics and democracy, focusing on three key aspects: Islam's potential to influence social, economic, and political dynamics; the role of Islamic community organizations like Muhammadiyah and Nahdlatul Ulama in supporting inclusive democracy; and the interpretation and orientation of these organizations post-reform towards democracy. Islamic community organizations serve as pillars of civil society and strategic forces in shaping a more just political order. The research uses a literature review method to identify, evaluate, and synthesize relevant literature to provide insights into the relationship between Islam and democracy in Indonesia. The findings show that Islamic politics address the failures of established ideologies like nationalism, socialism, and capitalism by leveraging values of social justice, brotherhood, and welfare. Post-reform, Islamic organizations like Muhammadiyah and NU have shown substantial contributions to strengthening inclusive democracy through tolerance, diversity, and political stability. However, the study also highlights the challenges posed by extremist groups that reject democracy and use violence as a means of struggle.